The Sargasso Sea High Seas EBSA After Ten Years: Is It Still Relevant and How Has It Helped Conservation Efforts? - Roe, Howard S. J.; Freestone, David; Sapsford, Fae (Frontiers in Marine Science, 2022)
The Sargasso Sea is a high seas ecosystem located within the North Atlantic Subtropical Gyre. The floating Sargassum macroalgae for which it is named support a diverse and productive ocean ecosystem. The floating mats and windrows of Sargassum house distinct communities of animals including endemic species, and provide shelter, nursery areas and food for many others including juvenile turtles, fish, and birds. A decade ago, in 2012, the two million square mile core area of the Sargasso Sea was “described” by the parties to the Convention on Biological Diversity (CBD) as an Ecologically or Biologically Significant Marine Area (EBSA), having scored highly on six of the seven designated criteria. At the time it was the largest high seas EBSA to be so described. This paper reviews the scientific evidence supporting the finding that it meets the rigorous criteria for an EBSA and assesses whether there have been major changes in the decade since. It puts this in the context of the work of the Sargasso Sea Commission and the Hamilton Declaration Signatories to “conserve the Sargasso Sea for the benefit of present and future generations” and assesses the extent to which being an EBSA has assisted with these conservation efforts.